Systemic fungal infection in a dog: a unique case in Ireland - Atencia, Sabela (BioMed Central, 2014)
A three year old male entire Staffordshire bull terrier was referred to University College Dublin Veterinary Hospital, with a two week history of fever, inflammation of the right hock, lameness on the right hindlimb, peripheral lymphadenopathy and gastrointestinal signs (vomiting and diarrhoea). For the preceding three months the dog had been treated for atopic dermatitis with oral ciclosporin (5 mg/kg, PO, q 24 hours). Cytological analysis of the affected lymph nodes demonstrated fungal-like organisms predominantly contained within macrophages. Subsequent fungal culture and microscopic identification confirmed the presence of a Byssochlamys sp. This fungus is a saprophytic organism which has been associated with mycotoxin production. It has not previously been identified as a cause of systemic infection in animals or humans. Ciclosporin was discontinued, and a second generation triazole, voriconazole prescribed at a dose of 6 mg/kg for the first two doses, and continued at 3 mg/kg every 12 hours for six months. There was an excellent response. Follow-up examination five weeks after treatment was completed confirmed remission of the disease. The dog remains alive and well three years later. The present case represents an unusual fungal infection in a dog secondary to immunosuppressive therapy with ciclosporin. Such a possibility should be considered in animals presenting with signs consistent with systemic infection when receiving immunosuppressive medication.